In-hospital and long-term mortality in patients with arrhythmic storm. (26th April 2021) - Garcia-Arribas, D; Lopez De Sa, E; Rosillo, S; Caro, J; Armada, E; Carrion, I; Ferrera, C; Noriega, FJ; Viana, A
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Beca para la Formación e Investigación en Cuidados Críticos Cardiológicos concedida por la Asociación de Cardiopatía Isquémica y Cuidados Críticos Cardiológicosde la SEC Introduction: Available data on arrhythmic storm (AS) is usually obtained from retrospective observational studies based on series of patients (pts) with ICD or who undergo ablation. Therefore, selection bias limits the evidence regarding mortality and prognosis of this entity. Purpose/ Methods Describe in-hospital and long-term mortality of pts admitted between 2006 and 2020 for AS in the Acute Cardiac Care Unit (ACCU) of 2 tertiary hospitals in Spain. Results: A total of 190 episodes of AS in 169 pts were retrospectively analysed. Baseline characteristics are depicted in Table 1. In-hospital mortality was 18.9%. Mortality in STEMI related AS was 44.2%, while in the rest of aetiologies was 6.1% (p < 0.001). In-hospital cause of death was heart failure or cardiogenic shock (32.4%), refractory AS (20.6%), cardiac arrest due to pulseless activity (8.8%), severe postanoxic encephalopathy (14.7%), septic shock (8.8%), others (14.7%). long-term follow-up was obtained in 154 pts. Among those patients who survived after the first episode of AS, median follow up was 2.85 years. Long term mortality was 49.7%. Long-term survival did not differ among STEMI related AS (8.30 years, 95% CI 5.62 to 10.98) and the rest of aetiologies (6.91 years, 95% CI 5.75 to 8.07), Log rank 0.33. Kapplan-Meier survival curves are presented in Figure 1. Long-term cause of death was AS (8.3%), heart failure or cardiogenic shock (14.6%), cardiac arrest due to pulseless activity (4.2%), STEMI (2.1%), stroke (8.3%), cancer (10.4%), pneumonia and sepsis (22.9%) and unknown (29.2%). Conclusion: In-hospital mortality in patients with AS requiring admission to an ACCU differs depending on the aetiology being worst in STEMI related AS. Long term mortality remains high and do not depend on the ethiology.